Adjunctive albuterol enhances the response to enzyme replacement therapy in late‐onset Pompe disease. Issue 5 (17th January 2014) - Koeberl, Dwight D.; Austin, Stephanie; Case, Laura E.; Smith, Edward C.; Buckley, Anne F.; Young, Sarah P.; Bali, Deeksha; Kishnani, Priya S.
ABSTRACT: Effective dosages for enzyme replacement therapy (ERT) in Pompe disease are much higher than for other lysosomal storage disorders, which has been attributed to low cation‐independent mannose‐6‐phosphate receptor (CI‐MPR) in skeletal muscle. We have previously demonstrated the benefit of increased CI‐MPR‐mediated uptake of recombinant human acid‐α‐glucosidase during ERT in mice with Pompe disease following addition of albuterol therapy. Currently we have completed a pilot study of albuterol in patients with late‐onset Pompe disease already on ERT for >2 yr, who were not improving further. The 6‐min walk test (6MWT) distance increased in all 7 subjects at wk 6 (30±13 m; P =0.002), wk 12 (34±14 m; P =0.004), and wk 24 (42±37 m; P =0.02), in comparison with baseline. Grip strength was improved significantly for both hands at wk 12. Furthermore, individual subjects reported benefits; e.g ., a female patient could stand up from sitting on the floor much more easily (time for supine to standing position decreased from 30 to 11 s), and a male patient could readily swing his legs out of his van seat (hip abduction increased from 1 to 2+ on manual muscle testing). Finally, analysis of the quadriceps biopsies suggested increased CI‐MPR at wk 12 ( P =0.08), compared with baseline. With the exception of 1 patient who succumbed to respiratory complications of Pompe disease in the first week, only mild adverse events have been reported, including tremor, transient difficulty falling asleep, and mild urinary retention (requiring early morning voiding). Therefore, this pilot study revealed initial safety and efficacy in an open label study of adjunctive albuterol therapy in patients with late‐onset Pompe disease who had been stable on ERT with no improvements noted over the previous several years.—Koeberl, D. D., Austin, S., Case, L. E., Smith, E. C., Buckley, A. F., Young, S. P., Bali, D., Kishnani, P. S. Adjunctive albuterol enhances the response to enzyme replacement therapy in late‐onset Pompe disease. FASEB J . 28, 2171–2176 (2014). www.fasebj.org